Gravity Chains: Estimating bilateral trade flows when parts and components trade is important - Richard E. Baldwin; Daria Taglioni (Journal of Banking and Financial Economics)
Trade is measured on a gross sales basis while GDP is measured on a net sales basis, i.e. value added. The rapid internationalisation of production in the last two decades has meant that gross trade flows are increasingly unrepresentative of the value-added flows. This fact has important implications for the estimation of the gravity equation. We present empirical evidence that the standard gravity equation performs poorly by some measures when it is applied to bilateral flows where the parts and components trade is important. We also provide a simple theoretical foundation for a modified gravity equation that is suited to explaining trade where international supply chains are important.